Crafts of the Khiva Khanate period: types and products of textiles and tanning (XVI-XVIII centuries) (Eurasian Journal of History, Geography and Economics, 2022)
The article provides information about the types of crafts that existed in the Khiva Khanate in the XVIth-XVIIIth centuries, about the products made by craftsmen and the raw materials used in them.